Grau de incapacidade física e percepção de qualidade de vida de idosos portadores de hanseníase - Ramos, Mariana Pereira (2014)
This study aimed to evaluate the degree of physical disability and perception of quality of life in elderly patients with leprosy in a House of Health of Minas Gerais. This is a descriptive, cross-sectional, where 50 patients with leprosy were evaluated, 60 years or older who already did the full treatment of the disease and were cured. Of these, 54.0% were female and ages ranged from 60 to 90 years, observing a higher frequency in the range 70-79 years (58.0%). In relation to the degree of physical disability, 54.0% were classified as grade II, 34.0% grade I and 12.0% with zero degree. The body areas with higher levels of commitment were the feet (44.0%), the hands (40.0%) and, lastly, the eyes (32.0%). The main physical onsets were presented corneal opacity and cataract eyes (38.0%), involvement of the ulnar nerve in the upper limbs (64.0%) and a decrease or loss of sensation in the feet (84.0%). Most participants considered the perception of quality of life as you need to improve or regulate, in both questionnaires, WHOQOL BREF (52.0%) and WHOQOL OLD (78.0%). The most impaired aspects in relation to the domains and facets of the questionnaires on quality of life were intimacy, social participation and physical. The facet death and dying and the social relationships domain showed the best results, with the majority of the elderly (64.0%) considered as good and very good aspects evaluated by facet death and dying and 54.0% considered as good aspect assessed by social relationships domain. Given the results presented, it is necessary to involve elderly patients with leprosy, along with their families and professionals of the House of Health in the search for effective health promotion and improvement of their living conditions shares. The actual work of primary care in the active search for patients with leprosy and their communicants are of fundamental importance in the prevention of physical disability and the maintenance of quality of life and health of patients with leprosy. Keywords: Leprosy; Health promotion; Disability; Quality of life.